(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The aims of the research are to identify the effective use of translation techniques when transferring the texts from English into Indonesian and to know how important translation techniques are to producing the translation quality of the nominal group. To achieve the objectives of the research. The data of English nominal groups and their translations were collected and analyzed to determine what translation techniques were used by the translator to translate the nominal groups and how the translation techniques impacted the translation results. To decide what translation techniques to use, we had a focus group discussion with the raters, linguists, and academic translation experts.